Symptomatic Early Congenital Syphilis: A Common but Forgotten Disease - Machiraju Vasudeva Murali; Cherukuri Nirmala; Jampana Venkateswara Rao (Hindawi Limited, 2012)
Congenital syphilis is a severe, disabling infection often with grave consequences seen in infants. It occurs due to the transmission of the disease from an infected mother to the unborn infant through the placenta. This long forgotten disease continues to affect pregnant women resulting in perinatal morbidity and mortality. The continuing prevalence of this disease reveals the failure of control measures established for its prevention. We put forth a case of symptomatic congenital syphilis presenting with skeletal manifestations at birth, a rare finding in literature. The report stresses upon the importance of implementing the World Health Organization's recommendation that all pregnant women should be screened for syphilis in the first antenatal visit in the first trimester and again in the late pregnancy.